To Become Images, to Be Images - Sainza Fraga, Barbara (Re-visiones, 2024)
Beginning with the zero production as a procedure of substitution of the camera operator, this text tries to make a path in which appear some magnitudes of the socialized and industrialized images derived from the above mentioned disappearance. Since the idea that turns out our ordinary acts into movie action, it is an intention of this text to develop the idea inherent in the above mentioned affirmation, it is carried out another displaceent because of which is caused another conversion, a second faint, that of the spectator: emergent point, field of practical actions of an imaginary dimension -of a life away form life- transferred, dreaming, hallucinated because of which we do not make images, but we become images ourselves, we are images.